Growth mindset development in design-based makerspace: a longitudinal study. Issue 2 (13th May 2021) - Vongkulluksn, Vanessa W.; Matewos, Ananya M.; Sinatra, Gale M.
Abstract: Growth mindset plays an important role in students' motivation for learning. Students who believe that their abilities are malleable are more likely to set mastery goals and to persist when encountering difficulties. Design-based makerspace – or a makerspace structured with design-based learning components – has many features known to improve growth mindset. The present study examined how growth mindset of 3rd–6th grade students developed over 2 years in a design-based makerspace course. Growth modeling was used to examine trajectories of students' growth mindset as well as its two associative factors – self-efficacy and creative mindset. Results showed that students' growth mindset initially decreased slightly in the first year, but significantly improved during the intervening period and remained high throughout the second year. Students with higher creative mindset showed more adaptive growth mindset trends. Our study contributes to an understanding about how makerspace experiences may contribute to growth mindset development.